The Effect of Credit Restructuring and Risk Management on The Financial Performance of The Banking Sector Listed on The Indonesia Stock Exchange for The Period 2016 – 2020 - Alianti, Fiori Nika; Meini, Zumratul; Digdowiseiso , Kumba (CV ODIS, 2023)
This study aims to determine the effect of credit restructuring and risk management on the financial performance of the IDX-listed banking sector for the period 2016 - 2020. The samples used in this study were 116 samples using secondary data from the annual reports of companies listed on the Indonesia Stock Exchange in the 2016-2020 period. The sampling method uses the purposive sampling method. For testing using multiple linear regression analysis using Statistical Product and Service Solution (SPSS) software Version 25.0. The results of multiple linear regression show that the credit restructuring variable does not affect financial performance, the credit risk variable does not affect financial performance, the liquidity risk variable has a negative and significant effect on financial performance, and the operational risk variable has a negative and significant effect on financial performance.